2006
DOI: 10.1037/0096-1523.32.6.1380
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of bottom-up and top-down motion processes to perceived position.

Abstract: Perceived position depends on many factors, including motion present in a visual scene. Convincing evidence shows that high-level motion perception--which is driven by top-down processes such as attentional tracking or inferred motion--can influence the perceived position of an object. Is high-level motion sufficient to influence perceived position, and is attention to or awareness of motion direction necessary to displace objects' perceived positions? Consistent with previous reports, the first experiment rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 113 publications
5
22
0
Order By: Relevance
“…To determine whether the motion-energy signals evoked by the Plunger stimuli were being pooled, we exploited the ''motion drag'' effect, in which the perceived position of peripherally-presented objects is spatially displaced in the direction of motion (Scarfe & Johnston, 2010;Whitney, 2006;Whitney & Cavanagh, 2000;Whitney et al, 2003). To do this, we first established that the global TAM array induced motion drag.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether the motion-energy signals evoked by the Plunger stimuli were being pooled, we exploited the ''motion drag'' effect, in which the perceived position of peripherally-presented objects is spatially displaced in the direction of motion (Scarfe & Johnston, 2010;Whitney, 2006;Whitney & Cavanagh, 2000;Whitney et al, 2003). To do this, we first established that the global TAM array induced motion drag.…”
Section: Resultsmentioning
confidence: 99%
“…The displacement of the flash was greatest when it was aligned in time and location with the physical trajectory endpoint. Nevertheless, there was a shift in the perceived position of the flash that remained at about 1/10 th the maximum even when it was presented off the moving texture rather than on it (e.g., as in the flash drag stimulus, Whitney & Cavanagh, 2000a; Durant & Johnston, 2004; Roach & McGraw, 2006; Shim & Cavanagh, 2005; Whitney, 2006), or at the midpoint of the trajectory rather than at the reversal point, or out of alignment with the local contrast edges in the moving trajectory, rather than in alignment.…”
Section: Experiments 4: Is Attention Required?mentioning
confidence: 99%
“…Specifically, the flash grab effect requires attention (Figure 15) whereas the flash drag can be seen with or without attention. In particular, the flash drag is seen with attentive tracking (Shim & Cavanagh, 2005) and transformational apparent motion (Whitney, 2006) where there is no low-level motion signal. It is also seen for motion that cannot be tracked attentively either because it is too fast (Whitney & Cavanagh, 2000a) or because it is reversing too rapidly and unpredictably (Fugiake et al, 2011).…”
Section: Experiments 4: Is Attention Required?mentioning
confidence: 99%
“…Subsequently, several papers have found evidence for a contribution from the high-level motion system to this position shift illusion in the absence of low-level motion energy. These studies used either motion viewed through apertures (Watanabe, Nijhawan, & Shimojo, 2002), inferred motion (Watanabe, Sato, & Shimojo, 2003), or apparent motion (Shim & Cavanagh, 2004; Whitney, 2006). Other studies have demonstrated the position shift for stimuli that could only drive the low-level motion system (Harp, Bressler, & Whitney, 2007; Whitney, 2005).…”
Section: Introductionmentioning
confidence: 99%